Functional characterization of peroxiredoxins from the human protozoan parasite Giardia intestinalis. - Daniela Mastronicola; Micol Falabella; Fabrizio Testa; Leopoldo Paolo Pucillo; Miguel Teixeira; Paolo Sarti; Lígia M Saraiva; Alessandro Giuffrè (PLoS Neglected Tropical Diseases, 2014)
The microaerophilic protozoan parasite Giardia intestinalis, causative of one of the most common human intestinal diseases worldwide, infects the mucosa of the proximal small intestine, where it has to cope with O2 and nitric oxide (NO). Elucidating the antioxidant defense system of this pathogen lacking catalase and other conventional antioxidant enzymes is thus important to unveil novel potential drug targets. Enzymes metabolizing O2, NO and superoxide anion (O2 (-•)) have been recently reported for Giardia, but it is yet unknown how the parasite copes with H2O2 and peroxynitrite (ONOO(-)). Giardia encodes two yet uncharacterized 2-cys peroxiredoxins (Prxs), GiPrx1a and GiPrx1b. Peroxiredoxins are peroxidases implicated in virulence and drug resistance in several parasitic protozoa, able to protect from nitroxidative stress and repair oxidatively damaged molecules. GiPrx1a and a truncated form of GiPrx1b (deltaGiPrx1b) were expressed in Escherichia coli, purified and functionally characterized. Both Prxs effectively metabolize H2O2 and alkyl-hydroperoxides (cumyl- and tert-butyl-hydroperoxide) in the presence of NADPH and E. coli thioredoxin reductase/thioredoxin as the reducing system. Stopped-flow experiments show that both proteins in the reduced state react with ONOO(-) rapidly (k = 4×10(5) M(-1) s(-1) and 2×10(5) M(-1) s(-1) at 4°C, for GiPrx1a and deltaGiPrx1b, respectively). Consistent with a protective role against oxidative stress, expression of GiPrx1a (but not deltaGiPrx1b) is induced in parasitic cells exposed to air O2 for 24 h. Based on these results, GiPrx1a and deltaGiPrx1b are suggested to play an important role in the antioxidant defense of Giardia, possibly contributing to pathogenesis.